Protective Effects of Cinnamon on oxidative stress and nephron toxicity induced by Lead Acetate in Male Albino (Rattus rattus) - Mohammed, Sulaf Mustafa (Sulaimani Journal for Pure and Applied Sciences, 2018)
Cinnamon the eternal tree of tropical medicine is one of the most important and spices used daily by people all over the world for preparing delicious foods. This plant considers as a rich source of antioxidants. Therefore, the current research was aimed to study the protective effects of cinnamon against oxidative stress and, nephron-toxicity induced by Lead acetate in male rats. For this purpose, 35 male rats have been used, they were randomly allotted to five groups each with seven rats; The first group was used as a control negative and was fed on the standard diet and tap water. The second group was injected intraperitoneally (IP) (20 mg/kg BW) with lead acetate. The third group was treated with 10% cinnamon dissolved drinking water and injected with 20 mg/kg BW lead acetate. The fourth group was treated with 20% cinnamon dissolved in drinking water and injected with lead acetate (20 mg/kg BW). The fifth group was treated with 40% cinnamon dissolved in drinking water and injected with lead acetate (20 mg/kg.bw). After 10 weeks of the experiment, blood collected for estimation of superoxide dismutase (SOD), levels of total glutathione (GSH), malonaldehyde (MDA), serum creatinine and blood urea. The second group results revealed that lead acetate has a negative effect on rats by significantly decreasing the level of SOD, total GSH, blood urea and creatinine and significantly increasing the level of MDA in the serum of rats. The protective activity of cinnamon against oxidative stress and nephrotoxicity was dose-dependent because the best result has been obtained from third group Pb+10% cinnamon by improving levels of SOD, GSH, blood urea, serum creatinine concentration. Positive impacts of cinnamon decreased at a higher concentration 20% cinnamon and 40% cinnamon. As a result, cinnamon at low concentration has a great impact on oxidative stress and nephron-toxicity.
Keywords: Lead acetate; nephrontoxicity; oxidative stress; antioxidant; cinnamon; renal function; lipid peroxidation